Relationships among superantigen toxin gene profiles, genotypes, and pathogenic characteristics of Staphylococcus aureus isolates from bovine mastitis - Wang, Dong; Zhang, Limei; Yong, Changfu; Shen, Mingliang; Ali, Tariq; Shahid, Muhammad; Han, Kun; Zhou, Xuezhang; Han, Bo (Journal of dairy science, 2017)
Staphylococcus aureus is one of the major etiological agents of bovine mastitis, harboring a wide variety of staphylococcal superantigen (SAg) toxin genes. The SAg toxin genes are reported to be closely associated with the pathogenicity of the Staph. aureus causing the bovine mastitis. This study was conducted to investigate SAg toxin gene profiles and to assess the relationships among SAg toxin genes, genotypes of Staph. aureus, and their pathogenic properties. A total of 327 quarter milk samples were collected from bovine mastitis cases for isolation and identification of pathogens. In total, 35 isolates were identified as Staph. aureus, and the prevalence of Staph. aureus in milk samples was 13.6% (35/256). Polymerase chain reaction (PCR) and randomly amplified polymorphic DNA (RAPD) assays were used to detect the SAg toxin genes and to genotype Staph. aureus strains isolated from milk samples of bovine mastitis in 10 dairy herds located in Ningxia, China, respectively. The results showed that among the Staph. aureus isolates (n = 35), 71.4% (n = 25) of isolates carried at least one SAg toxin gene. In total, 18 SAg genes and 21 different gene combination patterns were detected among these isolates. The most common SAg genes in Staph. aureus isolates were sei, sen, and seu (44.0% each), followed by seo, tst, and etB (28.0% each), etA (24.0%), sem and sep (16.0% each), seb, sec, sed, and sek (12.0% each), and sea and seh genes (8.0% each); the seg, sej, and ser genes were present in 4.0% of the isolates. Three gene combinations were found to be related to mobile genetic elements that carried 2 or more genes. The egc-cluster of the seg-sei-sem-sen-seo genes, located on the pathogenicity island Type I υSaβ, was detected in 16% of isolates. Interestingly, we observed 6 RAPD genotypes (I to VI) in Staph. aureus isolates, and 2 of these genotypes were strongly associated with the severity of bovine mastitis; there was a close relationship between the RAPD genotypes and SAg genes. Isolates of RAPD type III were more frequently associated with clinical and subclinical mastitis, whereas strains of type VI were mostly related to subclinical mastitis. In addition, SAg genes were related to severity of bovine mastitis. We conclude that an obvious relationship exists among RAPD genotypes, SAg toxin genes, and severity of bovine mastitis.